Technology-Driven SCM Practices and Operational Efficiency in The ‎Milk Sector: A PLS-SEM Study - Basha, S. Ismail; A. Vasumathi, Dr (International Journal of Accounting and Economics Studies, 2025)
This study investigates the consequential interplay between SCMP (Supply Chain ‎Management Practices) and integration technology within milk sectors, with a primary focus ‎on their combined impact on operational efficiency. In an era marked by rapid technological ‎advancements, the milk sector stands to benefit significantly from the strategic incorporation ‎of innovative SCM practices and technology adaptation. Through a comprehensive analysis of ‎case studies and empirical data, this research focuses on delineating how technology-driven ‎SCM initiatives can revolutionize and optimize various facets of the milk supply chain. The ‎findings aim to shed light on the intricate relationships between these key variables and their ‎direct influence on operational efficiency metrics. As the milk sector grapples with increasing ‎demands and global complexities, understanding and harnessing the synergies between SCM ‎practices and technological adaptation becomes essential for fostering resilience, reducing ‎operational costs, and ultimately elevating the overall performance of the milk supply chain. ‎The integration of advanced technologies in SCM processes has the potential to revolutionize ‎the way milk operations are managed, from production to distribution‎.
Keywords: Operational Efficiency; Supply Chain Management; Supply Chain Management Practices; Technology Adoption‎.